Screening and brief intervention in high schools: School nurses' practices and attitudes in Massachusetts. Issue 3 (July 2017) - Lunstead, Julie; Weitzman, Elissa R.; Kaye, Dylan; Levy, Sharon
Background: Screening, brief intervention, and referral to treatment (SBIRT) is recommended as a strategy to prevent or reduce adolescent substance use. Offering SBIRT in schools may provide an opportunity to reach adolescents not accessing primary care. The objective is to assess school nurses' attitudes and practices regarding adolescent SBIRT. Methods: The authors administered electronically and in person a questionnaire including 29 items on SBIRT attitudes and practices to school nurses registered for the Northeastern University's School Health Institute Summer Program in Massachusetts ( N = 168). Survey questions were adapted from a questionnaire originally developed by the American Academy of Pediatrics. Results: One hundred and forty-four nurses completed the survey for a response rate of 85.7%. More than three quarters of the respondents (77.0%) were in favor of universal alcohol screening in schools. None of the respondents reported screening their students on a regular basis. More than half (64.4%) of nurses reported screening students; however, they did so only when they suspected alcohol use. During these instances, only 17.9% used a validated screening tool and almost all (98.2%) used face-to-face clinical interviews. When addressing alcohol use by a student, the large majority of respondents reported including the following recommended clinical strategies: asking about problems related to alcohol use (56.3%), explaining the harms of alcohol use (70.1%), and advising abstinence (73.6%). On average, respondents spend 5 to 10 minutes discussing alcohol use with their students. Conclusion: Survey respondents were supportive of universal alcohol screening in school, although few were doing so at the time. When respondents identified students using alcohol, their interventions were closely aligned with clinical recommendations for brief intervention. Implementation of SBIRT that focuses on standardized, annual screening has the potential to deliver high-quality care in this setting.